Peritoneal Equilibration Test and Patient Outcomes - Mehrotra, Rajnish (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Although a peritoneal equilibration test yields data on three parameters (4-hour dialysate/plasma creatinine, 4- to 0-hour dialysate glucose, and 4-hour ultrafiltration volume), all studies have focused on the prognostic value of dialysate/plasma creatinine for patients undergoing peritoneal dialysis. Because dialysate 4- to 0-hour glucose and ultrafiltration volume may be superior in predicting daily ultrafiltration, the likely mechanism for the association of peritoneal equilibration test results with outcomes, we hypothesized that they are superior to dialysate/plasma creatinine for risk prediction. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We examined unadjusted and adjusted associations of three peritoneal equilibration test parameters with all-cause mortality, technique failure, and hospitalization rate in 10,142 patients on peritoneal dialysis treated between January 1, 2007 and December 31, 2011 in 764 dialysis facilities operated by a single large dialysis organization in the United States, with a median follow–up period of 15.8 months; 87% were treated with automated peritoneal dialysis. RESULTS: Demographic and clinical parameters explained only 8% of the variability in dialysate/plasma creatinine. There was a linear association between dialysate/plasma creatinine and mortality (adjusted hazards ratio per 0.1 unit higher, 1.07; 95% confidence interval, 1.02 to 1.13) and hospitalization rate (adjusted incidence rate ratio per 0.1 unit higher, 1.05; 95% confidence interval, 1.03 to 1.06). Dialysate/plasma creatinine and dialysate glucose were highly correlated (r=−0.84) and yielded similar risk prediction. Ultrafiltration volume was inversely related with hospitalization rate but not with all-cause mortality. None of the parameters were associated with technique failure. Adding 4- to 0-hour dialysate glucose, ultrafiltration volume, or both did not result in any improvement in risk prediction with dialysate/plasma creatinine alone. CONCLUSIONS: This analysis from a large contemporary cohort treated primarily with automated peritoneal dialysis validates dialysate/plasma creatinine as a robust predictor of outcomes in patients treated with peritoneal dialysis.